Rreducible H-functions of two variables - Buschman, R. (Rev. Téc. Fac. Ing. Univ. Zulia)
A reduction formula for certain H-funtions of two variables to H-functions of one variable is obtained. A special case is the known reduction formula for Appell’s funcrions F2 the Gauss function 2F1.